Potential efficacy of dopaminergic antidepressants in treatment resistant anergic-anhedonic depression results of the chronic anergic-anhedonic depression open trial – CADOT - Dormegny-Jeanjean, Ludovic Christophe; de Billy, Clément; Mainberger, Olivier; Weibel, Sébastien; Schorr, Benoit; Obrecht, Alexandre; Landré, Lionel; Berna, Fabrice; Causin, Jean-Baptiste; Blanc, Frederic; Danila, Vlad; Tomsa, Mihaela; et al. (Frontiers in Psychiatry, 2023)
Introduction Among treatment-resistant depression (TRD), we identified anergic-anhedonic clinical presentations (TRAD) as putatively responsive to pro-dopaminergic strategies. Based on the literature, non-selective monoamine oxidase inhibitors (MAOI) and dopamine D2 receptor agonists (D2RAG) were sequentially introduced, frequently under the coverage of a mood stabilizer. This two-step therapeutic strategy will be referred to as the Dopaminergic Antidepressant Therapy Algorithm (DATA). We describe the short and long-term outcomes of TRAD managed according to DATA guidelines. Method Out of 52 outpatients with TRAD treated with DATA in a single expert center, 48 were included in the analysis [severity – QIDS (Quick Inventory of Depressive Symptomatology) = 16 ± 3; episode duration = 4.1 ± 2.7 years; Thase and Rush resistance stage = 2.9 ± 0.6; functioning – GAF (Global Assessment of Functioning) = 41 ± 8]. These were followed-up for a median (1st – 3rd quartile) of 4 (1–9) months before being prescribed the first dopaminergic treatment and remitters were followed up 21 (11–33) months after remission. Results At the end of DATA step 1, 25 patients were in remission (QIDS <6; 52% [38–66%]). After DATA step 2, 37 patients were in remission (77% [65–89%]) to whom 5 patients with a QIDS score = 6 could be added (88% [78–97%]). Many of these patients felt subjectively remitted (GAF = 74 ± 10). There was a significant benefit to combining MAOI with D2RAG which was maintained for at least 18 months in 30 patients (79% [62–95%]). Conclusion These results support TRAD sensitivity to pro-dopaminergic interventions. However, some clinical heterogeneities remain in our sample and suggest some improvement in the description of dopamine-sensitive form(s).